in Quantitative Aptitude edited by
315 views
1 vote
1 vote
If $5^{x}-3^{y}=13438$ and $5^{x-1}+3^{y+1}=9686$, then  $x+y$ equals _______
in Quantitative Aptitude edited by
13.4k points
315 views

1 Answer

1 vote
1 vote

Given that,

  • $5^{x} -3^{y}=13438 \quad \longrightarrow (1)$
  • $5^{x-1}-3^{y+1}=9686 \quad \longrightarrow (2)$

$5^{x} \implies x=1,2,3,4,5,6,7, \dots$

  • $5^{1}=5$
  • $5^{2}=25$
  • $5^{3}=125$
  • $5^{4}=625$
  • $5^{5}=3125$
  • $5^{6}=15625$
  • $5^{7}=78125$

$3^{y} \implies y=1,2,3,4,5,6,7,8, \dots$

  • $3^{1}=3$
  • $3^{2}=9$
  • $3^{3}=27$
  • $3^{4}=81$
  • $3^{5}=243$
  • $3^{6}=729$
  • $3^{7}=2187$
  • $3^{8}=6561$

Put the values of $x$ and $y$ in equation $(1)$ and $(2).$ And check which values of $x$ and $y$ are satisfies.

Now, lets take $x = 6,y = 7,$ and check

  • $5^{x}- 3^{y}=13438  \quad \longrightarrow (1)$
  • $ 5^{6}-3^{7}=13438$
  • $15625-2187=13438$
  • $13438 =13438\quad $ (The first  equation is satisfied)

Similarly, we can check for equation $(2).$

  • $5^{x-1}-3^{y+1}=9686  \quad \longrightarrow (2)$
  • $5^{6-1}-3^{7+1}=9686$
  • $5^{5}-3^{8}=9686$
  • $3125+6561=9686$
  • $9686=9686 \quad $ (The second equation is satisfied)

We get, the value of $x=6,y=7$

$\therefore x+y=6+7=13$

$\textbf{Second Method:}$

Given that,

  • $5^{x}-3^{y}=13438 \quad \longrightarrow (1)$
  • $5^{x-1}+3^{y+1}=9686 \quad \longrightarrow (2)$

We can rewrite the  equation $(2).$

  • $5^{x} \ast 5^{-1}+ 3^{y}\ast 3^{1}=9686$
  • $\frac{5^{x}}{5}+ 3^{y} \ast 3=9686  \quad \longrightarrow (3)$

We can multiply $`3\text{’}$  both sides in  equation $(1).$

  • $5^{x} \ast 3 – 3^{y} \ast 3=13438.3$
  • $5^{x} \ast 3 – 3^{y}\ast 3=40314 \quad \longrightarrow (4) $

By adding the  equation $(3)$ and $(4)$, we get

$\Rightarrow \frac{5^{x}}{5} +3^{y}\ast 3+5^{x}\ast 3-3^{y}\ast 3=9686+40314$

$ \Rightarrow 5^{x}\ast 5^{-1}+5^{x}\ast 3^{1}=50000$

$ \Rightarrow 5^{x} \left(5^{-1}+3^{1} \right)=50000$

$ \Rightarrow 5^{x} \left (\frac{1}{5}+3 \right)=50000$

$ \Rightarrow 5^{x} \left( \frac{16}{5} \right)=50000$

$ \Rightarrow 5^{x}= \frac{250000}{16}$

$ \Rightarrow 5^{x}=15625$

$ \Rightarrow5^{x} = 5^{6}$

$\implies \boxed{x=6}$

We can put the value of $`x\text{’}$ in equation $(1)$, we get

$\Rightarrow 5^{x}-3^{y}=13438$

$ \Rightarrow 5^{6}-3^{y}=13438$

$ \Rightarrow 15625-3^{y}=13438$

$ \Rightarrow -3^{y}=13438-15625$

$ \Rightarrow -3^{y} =-2187$

$\Rightarrow 3^{y}=2187$

$ \Rightarrow 3^{y}=3^{7}$

 $\Rightarrow \boxed{y=7} $

$\therefore$ The value of $x+y=6+7=13$

Correct Answer $:13$

edited by
10.3k points
Answer:

Related questions

Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true